ANALISIS CERITA HIKAYAT SI MISKIN MENGGUNAKAN MODEL TEUN A VAN DIJK - SRI RAHAYU RACHMAN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
This study aims to describe the form of text structure, social context, and social cognition about criticality in the story of